2016
DOI: 10.1016/j.immuni.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of the Transcription Factor IRF-3 Activates RIPA, the Apoptotic Pathway that Protects Mice from Viral Pathogenesis

Abstract: SUMMARY The transcription factor IRF-3 mediates cellular antiviral response by inducing the expression of interferon and other antiviral proteins. In RNA-virus infected cells, IRF-3’s transcriptional activation is triggered primarily by RIG-I-like receptors (RLR), which can also activate the RLR-induced IRF-3-mediated pathway of apoptosis (RIPA). Here, we have reported that the pathway of IRF-3 activation in RIPA was independent of and distinct from the known pathway of transcriptional activation of IRF-3. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
189
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(197 citation statements)
references
References 37 publications
6
189
2
Order By: Relevance
“…In fact, in addition to NF-B activation downstream of pathogen-associated recognition receptors, LUBAC negatively regulates RIG-I-mediated innate immune responses by targeting RIG-I, TRIM25, and IRF3 for degradation (60,61) and by disrupting the TRAF3-MAVS complex (62). LUBAC also promotes IRF3 linear ubiquitination at two specific sites to activate the RLR-induced IRF-3-mediated pathway of apoptosis (63). Thus, LUBAC seems to be an important player in modulation of innate immune responses through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in addition to NF-B activation downstream of pathogen-associated recognition receptors, LUBAC negatively regulates RIG-I-mediated innate immune responses by targeting RIG-I, TRIM25, and IRF3 for degradation (60,61) and by disrupting the TRAF3-MAVS complex (62). LUBAC also promotes IRF3 linear ubiquitination at two specific sites to activate the RLR-induced IRF-3-mediated pathway of apoptosis (63). Thus, LUBAC seems to be an important player in modulation of innate immune responses through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In search of the mechanism mediating MAVS-induced death, the authors found that HAV-induced death of infected hepatocytes depends on the transcription factors IRF3 and IRF7. Since HAVinduced liver damage is independent of IFNAR signaling, IRF3/7 may trigger death directly through its transcriptional activity on pro-apoptotic molecules like the BH3-only protein PMAIP1 [5] or in a transcription-independent fashion by interacting with mitochondrial Bax [6]. Hirai-Yuki et al provide compelling evidence in their study for the key role of MAVS in the control of hepatocyte infection with an RNA virus like HAV.…”
Section: Infection With Hepatitis Viruses Such As Hepatitis a Virus mentioning
confidence: 99%
“…S13). IRF3 can also induce apoptosis through a transcription-independent mechanism involving a direct interaction with mitochondrial Bax (34). However, this would not explain the rare apoptotic hepatocytes observed in Irf3 -deficient mice (fig.…”
mentioning
confidence: 99%